A new mealybug in the genus Pseudococcus Westwood (Hemiptera: Coccomorpha: Pseudococcidae) from North America, with a key to species of Pseudococcus from the New World - Ellenrieder, Natalia Von; Watson, Gillian (Zootaxa, 2016)
A mealybug species that feeds on Agave spp., Pseudococcus variabilis sp. n. (Hemiptera: Coccomorpha: Pseudococcidae), is described from North America. Its entry into the United States was likely via the horticultural trade on its host plants in the genus Agave (Liliales: Agavaceae). Descriptions and illustrations of the adult female and male, diagnosis from congeners in the New World, and a molecular characterization based on COI are provided, as well as a key to adult females of all Pseudococcus species recorded from the New World.